A drunk and disorderly country: a nationwide cross-sectional survey of alcohol use and misuse in Great Britain. Issue 1 (27th October 2011) - Craig, D G; Dakkak, M; Gilmore, I T; Hawkey, C J; Rhodes, J M; Sheron, N; ,
Abstract : Objectives: To explore current alcohol drinking patterns, behaviours and attitudes in Great Britain. Design and setting: Independent online cross-sectional survey. Patients and interventions: Survey of 2221 individuals from a representative panel. Main outcome measures and results: Excessive alcohol consumption is a widespread problem across Great Britain. Binge-drinking is common among 18–24 year olds, with 19% reporting drinking 10+ drinks on the same drinking day. 'Pre-loading' with alcohol at home before going out was reported by 30% of 18–24-year-old drinkers, of whom 36% get drunk twice or more a month, with 27% having injured themselves while drunk. Among older drinkers, 25% regularly drink to excess, 8% drink seven or more drinks on a typical drinking day and 9% self-reported drink-driving. Male gender was an independent risk factor for heavy (>40 units/week) alcohol abuse (odds ratio 3.05 (95% CI 1.82 to 5.10)). Men (19%) were more likely than women (8%, p<0.001) to report binge-drinking, drink-driving (11% vs 3%, p<0.001), or to have missed work owing to alcohol consumption (12% vs 7%, p<0.001). Young drinkers said they were heavily influenced by overall alcohol price and drink promotions. Increasing average weekly alcohol consumption, age <55 years, male gender, never having been married and being in full-time employment were all independently associated with a history of alcohol-related self-harm. Alcohol abuse was not related to socioeconomic status. Conclusions: Alcohol abuse remains common across all socioeconomic strata and geographical areas of Great Britain. Minimum pricing strategies and interventions that target cheap on-trade alcohol products seem likely to bring major public health benefits.